Complete hydrocracking of dibenzyl ether over a solid acid under mild conditions. (1st November 2016) - Zhao, Mei-Xia; Wei, Xian-Yong; Qu, Meng; Kong, Jiao; Li, Zhan-Ku; Liu, Jing; Zong, Zhi-Min
Graphical abstract: Highlights: A novel solid acid was prepared by impregnating TFMSA onto MPZCA. Strong interaction exists between TFMSA and MPZCA. DBE was completely hydrocracked over TFMSA/MPZCA at 160 °C without H2 . The attack of H + on O atom in DBE could be vital for DBE hydrocracking. Abstract: A novel solid acid was prepared by impregnating trifluoromethanesulfonic acid (TFMSA) onto mesoporous ZrO2 coated attapulgite (MPZCA) via one-pot synthesis method. Dibenzyl ether (DBE) was used as a coal-related model compound to evaluate the catalytic activity of TFMSA/MPZCA for cleaving Calk –O bridged bonds in low-rank coals. The results show that DBE conversion over TFMSA/MPZCA could reach 100% at 160 °C in C2 H5 OH without charging H2 . TFMSA/MPZCA proved to be stable after 4 cycles with only slight loss in catalytic activity. Moreover, a H + transfer mechanism was proposed, which reasonably deduces possible pathways for DBE hydrocracking over TFMSA/MPZCA.